The effect of charismatic leaders on followers’ memory, error detection, persuasion and prosocial behavior: A cognitive science approach - Engelbert, Lara H.; van Elk, Michiel; Kandrik, Michal; Theeuwes, Jan; van Vugt, Mark (The Leadership quarterly, 2023)
Adopting a cognitive and follower-centric approach to charismatic leadership, we hypothesized that followers show lower levels of cognitive effort, reflected in superficial processing of factually correct information when listening to and viewing a charismatic leader. We conducted two experiments, using a 2 (charismatic versus neutral) × 2 (female versus male leader) between-subjects design and videos of trained actors delivering a speech. We examined the effects of leader charisma on (1a) followers’ ability to detect factually false information, (1b) accuracy to remember information from the leader (study 1, N = 100), (2a) the persuasiveness of factual messages, (2b) followers’ prosocial behavior and (2c) the mediating effect of the leader’s persuasiveness on followers’ prosocial behavior (study 2, N = 140). We did not find support for the effect of leader charisma on detecting false information, the persuasiveness of messages, or increased prosocial behavior among followers. We found an effect of leader charisma on memory. Participants recognized fewer messages in the charismatic compared to the neutral leader conditions. Exploratory analyses provided mixed results for an interaction effect of leader charisma and sex on detecting and remembering false information. Our studies offer first insights into the cognitive outcomes of the charismatic signaling process.